PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA PT PEGADAIAN (PERSERO) CABANG KENDAL - Hanin Welinda Destyani; Saryadi Saryadi (Universitas Diponegoro, 2016)
PT Pegadaian (Persero) is a state-owned company in Indonesia which is the core business of money lending services to the public on the law of pledge. The increasing number of competitors, spurring PT Pegadaian (Persero) Branch Kendal's able to provide a quality service to meet the needs and desires of customers through services oriented to customer satisfaction first. In its efforts to improve the quality of services, PT Pegadaian (Persero) Branch Kendal offers several services, such as loans, sales of gold bars, multi-line payments, and so forth. The purpose of this study to determine the effect of service quality (tangibles, reliability, responsiveness, assurance and empathy) toward customer satisfaction PT Pegadaian (Persero) Branch Kendal. The population in this study are customers of PT Pegadaian (Persero) Branch Kendal. The sample was 100 people, while sampling using purposive sampling techniques. The analysis technique used The people of Satisfaction Index (HPI) and the tool crosstab analysis, correlation, regression and hypothesis testing using t test and F test.The results of this study, seen from the calculation Community Satisfaction Index (HPI) found that the quality of service PT Pegadaian (Persero) Branch Kendal is A or graded Very Good and the results of this study indicate that the variable physical evidence, reliability, responsiveness, assurance, empathy individually affect the customer satisfaction PT Pegadaian (Persero) Branch Kendal and together show that the variables of physical evidence, reliability, responsiveness, assurance and empathy effect on customer satisfaction PT Pegadaian (Persero) Branch Kendal. Suggestions can be submitted is PT Pegadaian (Persero) Branch Kendal is a need to increase the cleanliness of the reception area, simplify administrative procedures for application and payment of credit, increasing the kecepattanggapan customer complaints and the need to increase empathy towards clients when providing care.